2021
DOI: 10.12998/wjcc.v9.i27.8260
|View full text |Cite
|
Sign up to set email alerts
|

Early acute fat embolism syndrome caused by femoral fracture: A case report

Abstract: BACKGROUND Fat embolism syndrome (FES) is a rare complication caused by the presence of fat particles in the microcirculation, which usually occurs within 12-72 h after trauma. At present, there have been few cases of fat embolism presenting within 3 h after trauma. Here, we report a case of femoral fracture complicated with an acute fat embolism caused by a car accident. CASE SUMMARY A 29-year-old woman with pain, swelling and limited movement of her left lower limb af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Among the reported fulminant FES cases, seven cases [13][14][15][16][17][18], including our case, were identified that developed less than 3 h after injury, with our case being the earliest after injury (Table 2). Most of the fulminant FES cases were severely ill. Another possible mechanism for cerebral fat embolization is that pulmonary fat embolization increases right atrial pressure, causing the leftover patent foramen ovale (PFO) to open, resulting in a right-to-left shunt, which allows fat droplets to flow into the arterial side and cause cerebral infarction [19].…”
Section: Discussionmentioning
confidence: 72%
“…Among the reported fulminant FES cases, seven cases [13][14][15][16][17][18], including our case, were identified that developed less than 3 h after injury, with our case being the earliest after injury (Table 2). Most of the fulminant FES cases were severely ill. Another possible mechanism for cerebral fat embolization is that pulmonary fat embolization increases right atrial pressure, causing the leftover patent foramen ovale (PFO) to open, resulting in a right-to-left shunt, which allows fat droplets to flow into the arterial side and cause cerebral infarction [19].…”
Section: Discussionmentioning
confidence: 72%